2019
DOI: 10.1016/j.techsoc.2019.101196
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder farmers' willingness to pay for scale-appropriate farm mechanization: Evidence from the mid-hills of Nepal

Abstract: This paper analyzes smallholder farmers' willingness to pay (WTP) for the purchase of scale-appropriate farm mechanization in the hill ecologies of Nepal using the case of mini-tiller technology: a small, 5–7 horsepower two-wheel tractor primarily used for agricultural land preparation. Using primary survey data from 628 randomly-selected households, we find that farm size, local wage rates, out-migration, access to credit services, and associations with agricultural cooperatives positively influence the WTP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…Female-headed households in Nepal doubled from 13% in 1995 to 26% in 2010 [66]. These circumstances have created an unprecedented workload and therefore, the need for reducing drudgery through agricultural mechanization in rural areas [67].…”
Section: Agenda Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…Female-headed households in Nepal doubled from 13% in 1995 to 26% in 2010 [66]. These circumstances have created an unprecedented workload and therefore, the need for reducing drudgery through agricultural mechanization in rural areas [67].…”
Section: Agenda Settingmentioning
confidence: 99%
“…In Nepal, male out-migration has created acute labor shortages during the peak farm seasons of planting and harvesting [1,62,65], which favor a high wage rate [67]. Major real wages in Nepalese agriculture increased by 22% in the last seven years compared to only 6% in the non-agricultural sector [66].…”
Section: Agenda Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Rahaman et al (2011) reported that the less number of labors per hectare is required to complete the production process by mechanized farm compared to traditional farms. Paudel et al (2019) showed that farm size, on-farm wage rates, access to credit serviceswere positively associated with willingness to pay for mini-tillers in mid-hills. Din and Khattak (2018) found the per acre productivity of mechanized farmers a little bit greater than the nonmechanized farmers.…”
mentioning
confidence: 99%